Local Wisdom of The Larung Tumpeng Tradition in Telaga Sarangan : A Resource for Learning Biodiversity and Developing Argumentation Skills - Catur Wardeny; Rinie Pratiwi Puspitawati; Lisa Lisdiana (Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This research aims to develop an e-book that explores biodiversity through the lens of the Telaga Sarangan Larung Tumpeng tradition, integrating local wisdom to enhance students' argumentation skills. Utilizing a development research method, the study follows the ADDIE framework, which consists of analysis, design, development, implementation, and evaluation phases. The data analysis technique employs validation tests and readability assessments for the e-book development outcomes, analyzed using a qualitative descriptive approach. The research utilized an e-book validation sheet evaluated by two lecturers—one an expert in content and the other in educational methods. Additionally, a readability test was conducted using Fry graphs. The validation results yielded an average score of 3.9, categorizing the e-book as very valid. This evaluation took into account various aspects such as presentation validity, content validity, and language validity. Additionally, the practicality of the e-book is evaluated through a readability test, which indicates a reading level appropriate for tenth-grade students. The e-book achieved a readability level of 12, classified as very positive and suitable for its intended audience. The study clearly demonstrated that the e-book focused on biodiversity, grounded in the local wisdom of the Larung Tumpeng tradition at Telaga Sarangan, is both valid and practical for enhancing the argumentation skills of X-grade high school students.